Peak current control of grid-feeding inverter with low voltage ride-through capability - Sepannur Bandri; Zuriman Anthony; Erhaneli Erhaneli; Fauzan Ismail (Universitas Ahmad Dahlan, 2024)
The grid-feeding inverter is the most popular choice for implementing a distributed generator (DG) in a photovoltaic (PV) system. Its role is to deliver active power with zero reactive power while connected to the grid. In most cases, the inverter is disconnected as soon as voltage sag disturbances occur, an operation that is known as an islanding mode. Recently, grid code regulations have been upgraded, allowing the inverter to remain connected to the grid and inject a certain amount of reactive power during voltage sags, provided that it meets grid code requirements. However, this can result in an increase in current injection by the inverter, which may cause overcurrent and damage the inverter if it exceeds the capability of the inverter. To control peak current during voltage sag disturbances, a proposed grid-feeding inverter attempts to detect voltage sag and calculate proportional injected active and reactive power. Once the disturbance has disappeared from the system, the inverters can be restored to normal operation. Prototype experiments have validated the ability of this system to control peak current during voltage sag while protecting the inverters.